TREATMENT OF CORONAVIRUS DISEASE (COVID-19): srpski - Milovanović, Dragan R.; Jankovic, Slobodan; Ruzic Zecevic, Dejana; Folic, Marko; Rosic, Nikola; Jovanovic, Danijela; Baskic, Dejan; Vojinovic, Radisa; Mijailovic, Zeljko; Sazdanovic, Predrag (Medicinski časopis, 2020)
Coronavirus disease (COVID-19) is caused by RNA virus of severe acute respiratory syndrome 2 (SARS-CoV-2) which is highly contagious to humans. Primary receptor for virus is probably angiotensin-converting enzyme 2. COVID-19 is a respiratory infection, primarily transmitted by droplets and close contact with diseased person. Estimated reproductive number (R0) is 2-2.5 and the mean incubation time is 5.2 days, ranging 1-14 days (95% confidence interval 4.1-7.0 days). The most common symptoms are: fever, dry cough, malaise, productive sputum and dyspnea, then, sore throat, headache, myalgia, arthralgia, fever and dizziness and, occasionally, confusion, rhinorrhea, nasal congestion, gastrointestinal symptoms, hemoptysis and conjunctival injection. Initial atypical manifestations are also known. Real-time reverse transcriptase polymerase chain reaction (rRT-PCR) assay is „gold“ diagnostic standard but specificity and sensitivity were not definitively established. The most common complications are: acute respiratory distress syndrome, acute liver damage, acute heart damage and arrhythmia, then, secondary infections, acute respiratory failure, acute renal impairment, sepsis and/or septic shock, pneumothorax, disseminated intravascular coagulation, acute heart failure and occasionally, rhabdomyolysis. Disease duration varies and in hospitalized patients it is estimated on 16-26 days (interquartile range 12-29 days), while global mortality rate is still unknown with certainty. Drugs against SARS-CoV-2 prescribed by empirical protocols (off-label use) are lopinavir/ritonavir, chloroquine and hydroxychloroquine, nitazoxanide, umifenovir, ribavirin, inhaled interferon alpha and new drugs of clinical trial stages are remdesivir, nafamostat i favipiravir. Proven drug prophylaxis of COVID-19 does not yet exist and vaccine against SARS-CoV-2 has not yet been developed.
Keywords: Srpski